On solutions of some delay Volterra integral problems on a half-line - Metwali, Mohamed M.A.; Cichoń, Kinga (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we study the existence of a.e. monotonic solutions of some general delay integral problems for both fractional and integer orders in the space of Lebesgue integrable functions on the interval R+ = [0;1) and in the space of locally integrable functions L1loc (R+). In particular, the uniqueness of solutions for considered problems is obtained.